Identification and validation of protective glycoproteins in Haemonchus contortus H11 - Hui Liu; Yao Zhang; Jiarui Li; Feng Liu; Lisha Ye; Xin Liu; Chunqun Wang; Min Hu (Frontiers in Immunology)
Barbervax is the first and only available vaccine to protect animals against Haemonchus contortus - one of the most pathogenic parasites of small ruminants. This vaccine contains a kind of native antigen called H11, a glycoprotein complex derived from integral gut of this parasite. Native H11 has been shown to induce high levels (72-95%) of protection, but single or two recombinant molecules of H11 are consistently unsuccessful. An increasing number of aminopeptidases related to H11 have been characterized in the past three decades, but little is known about which ones are the key contributors to protective immunity. Our recent work has revealed that the immunoprotective effect of H11 is primarily associated with its N-glycan moieties. To identify key immunoprotective glycoproteins derived from H11 antigen, we employed glycan-related protective IgG antibodies combined with LC-MS/MS analysis and identified five glycosylated H11 proteins: H11, H11-1, H11-2, H11-4, and H11-5. Subsequently, we utilized the baculovirus-insect cell expression system and successfully expressed four H11 recombinant proteins including rH11, rH11-1, rH11-2 and rH11-4, which demonstrated similar aminopeptidase activity and comparable high-mannose and di-fucosylated N-glycan structures to those found on native H11. Immunization of goats with a cocktail of four rH11s induced a 66.29% reduction (p > 0.05) in total worm burden and cumulative fecal egg counts. High level of anti-rH11s IgG which could inhibit H. contortus intestinal aminopeptidase activity and larval development. Collectively, our study identified glycoprotein antigens from H11 and assessed their protective efficacy of a recombinant cocktail expressed in insect cells. This work will provide valuable insights into further development of recombinant vaccines against parasitic nematodes.